Phase Transformations in Equiatomic Y–Cu Powder Mixture at Mechanical Milling - Dashevskyi, M.; Boshko, О.; Nakonechna, O.; Belyavina, N. (Металлофизика и новейшие технологии, 2017)
Mechanical alloying of the elemental powder mixture of copper and yttrium is performed in a high-energy planetary ball mill. The equiatomic YCu compound with full ordered CsCl-type structure is synthesized by use of powder-metallurgy methods for the first time. Phase transformations taking place at Y–Cu mixture milling are studied by x-ray diffraction methods. An expanded description of original software package for the automated DRON apparatus is presented. This software is used for analysis and interpretation of the obtained x-ray diffraction data. This package is intended for solving different tasks, namely: determination of both peak positions and integral intensities of the Bragg reflections by means of full profile analysis; carrying out the qualitative and quantitative phase analyses using PDF (Powder Diffraction File) data for phase identification and the least square method for lattice-constants’ refinement; testing the structure models and refining crystal-structure parameters (including coordinates, atomic position filling, texture, etc.). The effect of oxygen on the phase composition of milling products is analysed. В высокоэнергетической планетарной мельнице проведено механическое легирование эквиатомной смеси порошков меди и иттрия. Впервые эквиатомное соединение YCu с полностью упорядоченной структурой типа CsCl получено методами порошковой металлургии. Фазовые превращения, протекающие при размоле смеси Y–Cu, исследованы методами рентгеновской дифракции. Представлено расширенное описание комплекса программ, разработанного авторами для автоматического рентгеновского аппарата типа ДРОН. Это программное обеспечение предназначено для решения разнообразных задач, в частности, как для определения позиции пиков, так и интегральной интенсивности брэгговских изображений методом полнопрофильного анализа, проведения количественного и качественного фазового анализа с использованием банка данных для идентификации фазы и метода наименьших квадратов для уточнения постоянных решетки, тестирования структурных моделей и уточнения параметров кристаллической структуры (в том числе координат, заполнения атомных позиций, текстуры). Проанализировано влияние кислорода на фазовый состав продуктов размола. У високоенергетичному планетарному млині проведено механічне леґування еквіатомової суміші порошків міді й ітрію. Вперше еквіатомову сполуку YCu з повністю упорядкованою структурою типу CsCl одержано методами порошкової металурґії. Фазові перетворення, що мають місце при розмелюванні суміші Y–Cu, досліджено методами рентґенівської дифракції. Представлено розширений опис комплексу програм, розробленого авторами для автоматичного рентґенівського апарата типу ДРОН. Це програмне забезпечення призначено для вирішення різноманітних завдань, зокрема, визначення як позиції піків, так і інтеґральної інтенсивности Бреґґових відбиттів методою повнопрофільної аналізи, проведення кількісної та якісної фазових аналіз із використанням банку даних для ідентифікації фази та методи найменших квадратів для уточнення параметрів ґратниць, тестування структурних моделів та уточнення параметрів кристалічної структури (координати, заповнення атомових позицій, текстура тощо). Проаналізовано вплив кисню на фазовий склад продуктів розмелювання в планетарному кульовому млині.